Prevalence of APOL1 Risk Variants in Afro-Descendant Patients with Chronic Kidney Disease in a Latin American Country. (18th December 2019) - Duran, Carlos E.; Ramírez, Alejandro; Posada, Juan G.; Schweineberg, Johanna; Mesa, Liliana; Pachajoa, Harry; Estacio, Mayra; Manzi, Eliana; Aros, Vanessa; Díaz, Lorena; Garcia, Victor H.
Abstract : Introduction . In Colombia, the genetic background of the populations was shaped by different levels of admixture between Natives, European, and Africans. Approximately 35.363 patients have diagnosed chronic kidney disease and according to population studies, 10.4% of these patients are Afro-descendant. We aim to assess the frequency of APOL1 variants G1 and G2 in Afro-descendant patients with ESRD treated at la Fundacion Valle del Lili University Hospital in Cali, Colombia. Methods . This is an observational cross-sectional study. Afro-descendant patients with ESRD in waitlist or recipients of kidney transplant were evaluated. Clinical data were collected from the electronic medical records. Genotyping was carried out by amplification of the exon 7 of the APOL1 gene. For the identification of risk genotypes, the bioinformatics tool BLAST was used. Results . We enrolled 102 participants. The frequency of APOL1 risk variants was 67.2%, in which 24.5% ( n = 25) were G1 heterozygous and 5.8% ( n = 6) were G2 heterozygous and 37% of the patients had high-risk status with two alleles in homozygous (G1/G1 = 21 and G2/G2 = 3) or compound heterozygote (G1/G2 = 14) form.